Advances in Crop Genetic Improvement to Overcome Drought Stress: Bibliometric and Meta-Analysis - Patrícia Ferreira da Silva; Natália Cassa; Alberto Soares de Melo; José Dantas Neto; Luana Aparecida Menegaz Meneghetti; Alisson Silva Costa Custódio; Niclene Ponce Rodrigues de Oliveira; Tonny José Araújo da Silva; Edna Maria Bonfim-Silva; Sérgio Plens Andrade; Thiago Franco Duarte; Sávio da Silva Berilli; et al. (Agriculture, 2023)
Plant resistance to drought stress is a parameter that should be studied with more emphasis in the search for higher agricultural yields. In this scenario, research within breeding programs should be directed toward specific mechanisms of action and important agricultural crops in worldwide agribusiness. From this perspective, this study carried out a bibliographic investigation regarding the advances in genetic improvement aimed at drought stress in crops using a hybrid model of analysis of scientific articles. The analysis employed bibliometric parameters for qualitative and quantitative discussion of scientific production and the methodological process of systematic review for the synthesis of the results obtained. The work was divided into four stages: the search for articles in databases, meta-analysis, bibliometric analysis, and systematic analysis. Scientific articles were searched for on the Scopus, Scielo, and Web of Science databases within a 20-year timeframe. Most authors and institutions were from Asian countries, demonstrating the need for global expansion of research on the subject. With regard to the co-occurrence networks between the keywords used in the search, a focus was observed on the following terms: drought resistance, drought stress; drought, and drought tolerance. Evidently, the primary mechanism of tolerance or even resistance studied in breeding programs is associated with the expression of genes and genetically modified organisms that confer resistance to plants. Also, the crops addressed in the research retrieved are highly diverse.